Inside Microsoft® SQL Server® 2008: T-SQL Querying - Ben-Gan, Itzik (Microsoft Press, 2011)
Tackle the toughest set-based querying and query tuning problems—guided by an author team with in-depth, inside knowledge of T-SQL. Deepen your understanding of architecture and internals—and gain practical approaches and advanced techniques to optimize your code’s performance.